LUXURIOUS LIFE STYLE IN KEVIN KWAN'S NOVEL CRAZY RICH ASIANS - Eka Tri Purnama Sari; Andang Suhendi (Universitas Islam Sumatera Utara, 2023)
This study discussed the luxurious life style in Kevin Kwan's novel Crazy Rich Asians. The analysis focused on the lifestyle and characteristics of Asian rich people in Singapore. Twelve pieces of data are found, and the quotations are taken from the Crazy Rich Asians novel. It would be good evidence to expose the luxurious lifestyle represented by the Asian rich in Singapore. In collecting data, the theory from Raharjo and Silalahi was used, and some understanding and explanations from another expert. To analyse the data, the qualitative research method was applied. Therefore, this research method is considered very suitable for studying social phenomena such as the luxurious lifestyle depicted in the novel. There are four characteristics of a luxurious lifestyle depicted in Asian rich people. They are luxurious goods, luxurious activities, convenience, privacy, and exclusivity. Luxury goods as a feature of a luxurious lifestyle can be seen in the penchant of Asian rich people to buy luxury goods and jewellery, and to own luxury properties. Luxurious activity can be seen from the several activities. Convenience as the characteristic of luxurious activity can be seen from the use of luxurious facilities. The exclusive party at young’s family house, and the exclusivity of Nick’s house are presented to show privacy and exclusivity.